2009
DOI: 10.1542/peds.2009-2114
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use: A Pediatric Disease

Abstract: Tobacco use and secondhand tobacco-smoke (SHS) exposure are major national and international health concerns. Pediatricians and other clinicians who care for children are uniquely positioned to assist patients and families with tobacco-use prevention and treatment. Understanding the nature and extent of tobacco use and SHS exposure is an essential first step toward the goal of eliminating tobacco use and its consequences in the pediatric population. The next steps include counseling patients and family members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 80 publications
2
55
0
Order By: Relevance
“…However, previous research with adolescents has shown that good quality smoking-specific parental communication, demonstrated by a constructive and respectful manner, was a deterrent to smoking initiation among the adolescents [17,26]. Further, the overall approach of the parents in this study who discussed smoking with their children is consistent with recommendations and suggestions of authorities and experts in the field of youth smoking prevention [16,18,[27][28][29].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…However, previous research with adolescents has shown that good quality smoking-specific parental communication, demonstrated by a constructive and respectful manner, was a deterrent to smoking initiation among the adolescents [17,26]. Further, the overall approach of the parents in this study who discussed smoking with their children is consistent with recommendations and suggestions of authorities and experts in the field of youth smoking prevention [16,18,[27][28][29].…”
Section: Discussionsupporting
confidence: 69%
“…This is consistent with the perspective that a comprehensive, multichannel approach is required to achieve the greatest effect for smoking prevention [3,16]. Although parents thought that smoking prevention education needs to be carried out at the elementary level in school, some parents did not know whether smoking was addressed at their children's schools.…”
Section: Implications For Practice and Further Researchsupporting
confidence: 72%
See 2 more Smart Citations
“…12 However, there is an unmet need for the use of child tobacco prevention interventions in health care settings. Although the American Academy of Pediatrics (AAP) recommends that child tobacco prevention counseling should be given during medical visits, 13 few parents are receiving such interventions. 14ā€“18 …”
mentioning
confidence: 99%